Medication Reconcilation: “You will find it only if you look for it” - Munshi, Mohseenkhan; Saseedharan, Sanjith (Indian Journal of Pharmacy Practice)
Introduction: The process of identifying the most accurate list of all medications that the patient is taking, including name, dosage, frequency, and route, by comparing the medical record to an external list or container of medications obtained from a patient, hospital, or other provider is known as medication reconciliation. Medication error ranks at the top among the preventable errors and mishaps in the field of medicine. Objective: To study the frequency of errors as a result of medication reconciliation and to study role of clinical pharmacist in the picking up of the same. Methods: Repeat history taking and previous paper review by a dedicated clinical pharmacist over a period of 3 months in 20 bedded tertiary care ICU in Mumbai, India. For this purpose a dedicated medication reconciliation form was constituted. Drug interactions were also studied by the clinical pharmacist. Results: In 42.86% cases drug interactions were noted. In almost 8% of cases there was improper history taken while medication omission was noted in 2.98 % cases. In 45.23 % of cases no discrepancy was noted. Conclusion: Medication errors are very common in the intensive care unit and medical reconciliation by a dedicated clinical pharmacist may go a long way in preventing mishaps in medication use in our intensive care units.
Keywords: Discrepancies; Drug interaction; Medication reconciliation; Serious interaction; Significant interaction